2021
DOI: 10.2169/internalmedicine.5359-20
|View full text |Cite
|
Sign up to set email alerts
|

Anti-LGI1 Encephalitis Developing Immunoglobulin Responsive Orthostatic Hypotension after Remission

Abstract: Anti-leucine-rich glioma-inactivated 1 (LGI1) antibody is associated with limbic encephalitis. We herein report a patient with anti-LGI1 encephalitis who developed severe orthostatic hypotension (OH) responsive to immunoglobulin therapy five years after developing symptoms of encephalitis. A 71-year-old man presented with amnesia caused by limbic encephalitis. The symptoms of encephalitis improved partially without any immunotherapy. Five years later, he developed severe OH, and anti-LGI1 antibody was positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[9] The relationship between autoimmune encephalitis and hypotension is not clear, but several reports have shown that some patients with autoimmune encephalitis developed hypotension or orthostatic hypotension during treatment. [5][6][7]10,11] Among these patients, some had lesions involving the brainstem, [5,7,11] some had lesions in the hippocampal region, and some had specific autoantibodies. [5][6][7]11] These factors may be related to autonomic dysfunction or the influence of the central nervous system on peripheral vascular regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] The relationship between autoimmune encephalitis and hypotension is not clear, but several reports have shown that some patients with autoimmune encephalitis developed hypotension or orthostatic hypotension during treatment. [5][6][7]10,11] Among these patients, some had lesions involving the brainstem, [5,7,11] some had lesions in the hippocampal region, and some had specific autoantibodies. [5][6][7]11] These factors may be related to autonomic dysfunction or the influence of the central nervous system on peripheral vascular regulation.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]10,11] Among these patients, some had lesions involving the brainstem, [5,7,11] some had lesions in the hippocampal region, and some had specific autoantibodies. [5][6][7]11] These factors may be related to autonomic dysfunction or the influence of the central nervous system on peripheral vascular regulation. In our reported case, whether there is a possibility of autoimmune encephalitis following simple herpes virus encephalitis was considered, but due to the patient financial reasons, they refused to undergo further blood and CSF tests to detect related antibodies for autoimmune encephalitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation